2020
DOI: 10.3390/w12092524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined High Temperature and Waterlogging Stress at Booting Stage on Root Anatomy of Rice (Oryza sativa L.)

Abstract: In recent years, the alternating occurrence of high temperature and waterlogging disasters in South China has seriously reduced the yield of single cropping rice. Studying the changes in anatomical structure of the rice root system could provide theoretical basis for understanding the mechanisms of high temperature and waterlogging stress. To examine interactions between temperature and waterlogging stress, an experiment was set up in a growth chamber consisting of two temperatures (moderate, 30–34 °C and high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The increased N/FS ratio in 2020 compared to 2019 was also attributable to an increase in N uptake. Crop nutrient uptake is closely related to root growth (Huang, Chen, et al., 2016; Huang, Shan, et al., 2016), which is affected by several environmental factors including temperature (Zhen et al., 2020). The optimum temperature for root growth is 26.0–27.6°C in rice (Sánchez et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The increased N/FS ratio in 2020 compared to 2019 was also attributable to an increase in N uptake. Crop nutrient uptake is closely related to root growth (Huang, Chen, et al., 2016; Huang, Shan, et al., 2016), which is affected by several environmental factors including temperature (Zhen et al., 2020). The optimum temperature for root growth is 26.0–27.6°C in rice (Sánchez et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, combined stresses involving aeration stress have not had as much attention as other stresses. Studies on combined stresses that include aeration stress are aeration and salt stress in tomatoes [63], waterlogging and pathogen (Fusarium poae) stress on wheat and barley [64], and temperature and waterlogging stress on rice [65]. Given that concurrent stresses on a crop can produce a synergistic effect, the multiplicative and the most limiting stress approaches in models may be unrealistic and further research is needed to understand the various stress response pathways for combined stresses.…”
Section: Aeration Stressmentioning
confidence: 99%
“…The root phenotypes of crops can be altered to improve their high temperature resistance, which constitutes an important phenotypic characteristic. High temperature not only inhibits root development (Calleja-Cabrera et al, 2020;Hund et al, 2008) but also affects the absorption of water by the roots and accelerates root senescence, causing the lignified roots to elongate to almost the tip and resulting in a reduction in the root absorption area and rate of nutrient absorption (Zhen et al, 2020). Martins et al (2017) showed that, as the temperature increases, the roots could elongate faster to protect the meristems.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) found that the root length, root surface area, and root volume all decreased significantly. Under high temperature stress, the root diameter and root cortex thickness of rice were both significantly inhibited ( Zhen et al., 2020 ). A study also revealed that high temperatures reduced the root dry weight and R/S ratio but increased the specific root length, specific root surface area, and specific root volume ( Tahir et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%